Pengembangan Sistem Keamanan Rumah Berbasis IoT dengan Deteksi Intrusi Real-Time Menggunakan Sensor PIR dan Kamera, serta Notifikasi Otomatis melalui Aplikasi Mobile - Jarot Dian Susatyono; Febryantahanuji Febryantahanuji; Arsito Ari Kuncoro (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
Home security plays an essential role in contemporary life. As technology progresses, conventional security approaches are transitioning toward smarter, IoT-powered systems. This research introduces a real-time intrusion detection prototype combining a PIR sensor with an ESP32-CAM, integrated with Telegram for instant alerts. Once movement is detected, the system captures an image and sends both visual and text-based notifications to users, allowing for swift remote response. The system utilizes an ESP32 microcontroller linked to a PIR sensor and camera over Wi-Fi. Tests were performed to assess detection precision, response time, and system stability. The prototype achieved a 93% accuracy rate in detecting motion and delivered alerts with under a 5-second average delay. Image transmission through Telegram was successful, ensuring users receive visual proof in real-time. This solution is economical, intuitive to use, and suitable for household implementation. It offers a viable substitute to traditional CCTV by enabling proactive surveillance and remote interaction. Future enhancements could include cloud backup, facial recognition features, and smart home integrations.